Patterns of HIV/SIV Prevention and Control by Passive Antibody Immunization - Yamamoto, Hiroyuki; Matano, Tetsuro (Frontiers in Microbiology, 2016)
Neutralizing antibody (NAb) responses are promising immune effectors for control of human immunodeficiency virus (HIV) infection. Protective activity and mechanisms of immunodeficiency virus-specific NAbs have been increasingly scrutinized in animals infected with simian immunodeficiency virus (SIV), chimeric simian/human immunodeficiency virus (SHIV) and related viruses. Studies on such models have unraveled a previously underscored protective potential against immunodeficiency virus replication. Pre-challenge NAb titers feasibly provide sterile protection from SIV/SHIV infection by purging the earliest onset of viral replication and likely modulate innate immune cell responses. Sufficient sub-sterile NAb titers after established infection also confer dose-dependent reduction of viremia, and in certain earlier time frames augment adaptive immune cell responses and even provide rebound-free viral control. Here, we provide an overview of the obtained patterns of SIV/SHIV protection and viral control by various types of NAb passive immunizations and discuss how these notions may be extrapolated to NAb-based clinical control of HIV infection.